2017
DOI: 10.1504/ijsmile.2017.10006129
|View full text |Cite
|
Sign up to set email alerts
|

Social media adoption in higher education: a case study involving IT/IS students

Abstract: Social media adoption in higher education 63 activities based on social media, followed by the role of social influence. Based on the analysis, guidelines for planning social-media-based learning activities are proposed. Indications of further work complete the paper.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2017
2017

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 20 publications
0
1
0
Order By: Relevance
“…Customer Relationship Orientation includes dimensions such as perceived ease of use, perceived usefulness and attitudes towards use of Social CRM. In a study by Siakas et al (2017) in students' perception of using social media in education it was found that other factors important for social media adoption were infrastructure for using social media, social influence and experience of using social media were important factors for …”
Section: Social Crmmentioning
confidence: 99%
“…Customer Relationship Orientation includes dimensions such as perceived ease of use, perceived usefulness and attitudes towards use of Social CRM. In a study by Siakas et al (2017) in students' perception of using social media in education it was found that other factors important for social media adoption were infrastructure for using social media, social influence and experience of using social media were important factors for …”
Section: Social Crmmentioning
confidence: 99%